Analisis pengeluaran pangan dan non pangan, pola konsumsi, dan asupan energi dan protein di provinsi jawa timur sebelum dan selama pandemi Covid-19 - Fanisa Rachmi Siregar; Drajat Martianto; Ikeu Tanziha (Poltekkes Kemenkes Aceh, 2023)
Background: The impact caused by the Covid-19 pandemic has not only had an impact on health but also on social, economic and food activities. The impact of the pandemic on food security and nutrition, with restrictions on movement both within and across countries, will hamper food logistics and affect food availability. It can endangering family food security, especially for low-income families.Objectives: Assessing changes in expenditure patterns, calorie and protein intake, and food diversity in East Java Province before and during the Covid-19 pandemic.Methods: Cross-sectional study using secondary data is SUSENAS Data (National Social and Economic Survey) by the Central Bureau of Statistics for 2019, 2020 and 2021. The sample is 32,630 households divided into 5 income quintile groups, every 20% of the group with lowest to highest income. Microsoft Excel 2019 was used for data analysis then processed and data only analyzed descriptively.Results: Incline in household expenditure (food and non-food) during the pandemic compared to 2019 before the pandemic. The overall energy and protein intake declined (urban and rural) during the pandemic in 2020 but increased in 2021 compared to before. A similar trend was seen for the DDP score, which increased from 82,4 (2019) to 83,2 (2021) overall.Conclusion: Comparison before and during the Covid-19 pandemic in East Java Province is food expenditure has increased and non-food has decreased in 2020 and 2021. Energy, protein intake, and food diversity decreased during the pandemic especially in low-income. Low income households in rural and urban areas are indicated as food insecurity during the Covid-19 pandemic.